Neuroanatomical Alterations in Patients With Tinnitus Before and After Sound Therapy: A Voxel-Based Morphometry Study - Wei, Xuan; Lv, Han; Wang, Zhaodi; Liu, Chunli; Ren, Pengling; Zhang, Peng; Chen, Qian; Liu, Yawen; Zhao, Pengfei; Gong, Shusheng; Yang, Zhenghan; Wang, Zhenchang (Frontiers in Neuroscience, 2020)
According to previous studies, many neuroanatomical alterations have been detected in patients with tinnitus. However, few studies have reported on the morphological changes observed following sound therapy. To explore the brain anatomical alterations in patients with idiopathic tinnitus using voxel-based morphometry (VBM) analysis before and after effective 12 weeks sound therapy. The protocol was registered on ClinicalTrials.gov, ID: NCT02774122. In this study, we collected data from 27 matched healthy control (HC) individuals and 27 idiopathic tinnitus patients before and after 12 weeks of sound therapy by using adjusted narrow band sound. 3.0T MRI system and high-resolution 3D structural images were acquired with a 3D-BRAVO pulse sequence. Structural image data preprocessing was performed using the VBM8 toolbox. The Tinnitus Handicap Inventory (THI) score was acquired in the tinnitus group to assess the severity of tinnitus and tinnitus-related distress. Mann–Whitney U Test, Wilcoxon Signed-Ranks test, and Pearson’s correlation analysis were used in the statistical analysis. We found significantly decreased gray matter (GM) volume in the left thalami, right thalami, and cochlear nucleus among the tinnitus patients before sound therapy (baseline) compared to the HC group. However, we did not find significant differences in brain regions between the 12-week treatment and HC groups. According to the results of Wilcoxon Signed-Ranks test, the 12-week sound therapy group demonstrated significant greater brain volume compared with the baseline group among these brain regions. Decreased THI score and changed GM volume were not correlated. This is a useful study for observing the characteristics of neuroanatomical changes in patients with idiopathic tinnitus before and after sound treatment. The study characterized the effect of sound therapy on brain volume. It found that sound therapy had a normalizing effect on the bilateral thalami and cochlear nucleus. Clinical Trial Registration:www.ClinicalTrials.gov, NCT02774122.